2022
DOI: 10.1007/s10787-022-01027-6
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone and post-Covid-19 pulmonary fibrosis: invoked again for realistic goals

Abstract: Pirfenidone (PFN) is an anti-fibrotic drug with significant anti-inflammatory property used for treatment of fibrotic conditions such as idiopathic pulmonary fibrosis (IPF). In the coronavirus disease 2019 (Covid-19) era, severe acute respiratory syndrome 2 (SARS-CoV-2) could initially lead to acute lung injury (ALI) and in severe cases may cause acute respiratory distress syndrome (ARDS) which is usually resolved with normal lung function. However, some cases of ALI and ARDS are progressed to the more severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 100 publications
0
46
0
1
Order By: Relevance
“…Dumont et al found that CoQ10 had a potential effect on the reduction of βA pathology and improve cognition in the transgenic mice model of AD [ 70 ]. Thus, treatment with CoQ10 could be effective in the management of AD by reducing oxidative stress and inflammatory changes [ 71 , 72 , 73 ].…”
Section: Statins and Admentioning
confidence: 99%
“…Dumont et al found that CoQ10 had a potential effect on the reduction of βA pathology and improve cognition in the transgenic mice model of AD [ 70 ]. Thus, treatment with CoQ10 could be effective in the management of AD by reducing oxidative stress and inflammatory changes [ 71 , 72 , 73 ].…”
Section: Statins and Admentioning
confidence: 99%
“…The COVID-19 is caused by a novel single-strand RNA virus named the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 2 , 3 ]. The clinical feature of COVID-19 is asymptomatic or mild flu-like illness in the majority of cases [ 4 , 5 ]. However, about 15% of COVID-19 patients experienced features of acute viral pneumonia due to the propagation of acute lung injury (ALI).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, T2DM patients are at higher risk for the development of pulmonary hypertension and pulmonary embolism independent of smoking, hypertension, heart failure, and coronary artery disease. 53 , 77 The pathogenesis of this link has not yet been identified, although endothelial dysfunction, oxidative stress, and hypercoagulability in T2DM could be the association link. 53 , 54 Thrombotic events are augmented in T2DM patients due to platelet hyperreactivity, endothelial dysfunction, and uncontrolled activation of the coagulation pathway.…”
Section: Gdf15 and Diabetic Complicationsmentioning
confidence: 99%